Biological effectiveness of Carya illinoensis extracts for Meloidogyne incognita management - Garrido Cruz, Fabiola; Cepeda Siller, Melchor; Hernández Castillo Francisco Daniel; Ochoa Fuentes Yisa María; Cerna Chávez Ernesto; Margarita, Diana Morales Adame (Revista Mexicana de Ciencias Agrícolas, 2018)
The work was developed in 2012 at the Nematology Laboratory of the Universidad Autonoma Agraria Antonio Narro, with the aim of evaluating plant extracts derived hickory Carya illinoinensis (Wangenh) K. Koch, for the root-knot nematode Meloidogyne sp. Göldi (1889) management. Nematodes were obtained from potato tubers (Solanum tuberosum L.) Var. "Alpha", presenting symptoms. Identification of nematodes was performed and it was determined that corresponded to Meloidogyne incognita. Assessment study for the biological effectiveness of the extracts extracts were placed at different concentrations (1.0, 1.5 and 2%) using a population of 30 ± 5 Meloidogyne incognita specimens of assets, an experiment was completely randomized, with eleven treatments including control and f ive replications. Stereoscopic microscope at 24, 48 and 72 h of exposure to the extracts were observed to determine the percentage of mortality. Of the extracts tested, those with higher nematicidal activity were FIM8 (aqueous husk) with 89.16%, FIM6 (etanolítico husk) with 69.22%, and FIM7 (aqueous shell) with 60.77%, all these in the concentration of 2% and observation at 72 h of exposure to the extract.